The protective role of selenium against dental amalgam-induced intracellular oxidative toxicity through the TRPV1 channel in DBTRG glioblastoma cells - Derya CEYHAN; Kadriye Gorkem Ulu GUZEL; Bilal CIG (University of São Paulo, 2021)
Abstract Objective The exposure to mercury (Hg) from dental amalgams is a suspected causative factor in neurological diseases. This study investigated the toxic effects of two different amalgam compositions related to Hg and the protective effects of selenium against the toxic effects of Hg through the TRPV1 channel in the human DBTRG glioblastoma cell line. Methodology Six groups of the cells were organized. Analyses of cell viability, apoptosis, caspase 3 and caspase 9 activities, mitochondrial membrane depolarization, reactive oxygen species (ROS) production, and Western Blotting for protein expression levels were performed. Results Cell viability values were lower in amalgam with high copper (HCu) and low copper (LCu) groups independently of time but were increased by selenium and capsazepine (p<0.001 and p<0.05). Conversely, apoptosis rates, caspase 3 and caspase 9 expression, ROS formation, mitochondrial membrane depolarization, and protein expression levels were higher in the HCu and LCu groups but were decreased by selenium (p<0.001 and p<0.05). Conclusions Selenium combined with an amalgam of either HCu or LCu decreases the toxic effects created by Hg in human DBTRG glioblastoma cells.